CgSCD1 Is Essential for Melanin Biosynthesis and Pathogenicity of Colletotrichum gloeosporioides - Tan Wang; Dandan Ren; Han Guo; Xue Chen; Pinkuan Zhu; Haozhen Nie; Ling Xu (Pathogens, 2020)
Colletotrichum gloeosporioides, an important phytopathogenic fungus, mainly infects tropical fruits and results in serious anthracnose. Previous studies have shown that melanin biosynthesis inhibitor can inhibit the melanization of the appressoria of Magnaporthe grisea and Colletotrichum orbiculare, resulting in limited infection of the hosts. In this study, we identified and characterized a scytalone dehydratase gene (CgSCD1) from C. gloeosporioides which is involved in melanin synthesis. The CgSCD1 gene deletion mutant ΔCgscd1 was obtained using homologous recombination. The ΔCgscd1 mutant showed no melanin accumulation on appressoria formation and vegetative hyphae. Furthermore, the virulence of ΔCgscd1 was significantly reduced in comparison with the wild-type (WT) strain. Further investigations showed that the growth rate as well as germination and appressorium formation of ΔCgscd1 displayed no difference compared to the wild-type and complemented transformant Cgscd1com strains. Furthermore, we found that the appressorial turgor pressure in the ΔCgscd1 mutant showed no difference compared to that in the WT and Cgscd1com strains in the incipient cytorrhysis experiment. However, fewer infectious hyphae of ΔCgscd1 were observed in the penetration experiments, suggesting that the penetration ability of nonpigmented appressoria was partially impaired. In conclusion, we identified the CgSCD1 gene, which is involved in melanin synthesis and pathogenicity, and found that the melanization defect did not affect appressorial turgor pressure in C. gloeosporioides.